Akibat Hukum yang Timbul atas Terjadinya Kejadian Ikutan Pasca-Imunisasi pada Pelaksanaan Program Imunisasi Dasar Lengkap di Provinsi Banten - Asmawati Asmawati; Muhyi Mohas; Rani Sri Agustina (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to analyze the legal consequences arising from the occurrence of Post Immunization Adverse Events (KIPI) in the implementation of complete basic immunization in Banten Province. This type of research uses a normative juridical approach. Based on the results of the study, it is known that the legal consequences of the occurrence of AEFI in the implementation of immunization, both those who practice outside their authority and if an error occurs due to negligence can be subject to